TRANSPORTASI ANGKUTAN DARAT SEBAGAI KONTEKS UNTUK MEMBANTU SISWA SD MEMAHAMI OPERASI PENJUMLAHAN DAN PENGURANGAN - Kairuddin Kairuddin (Study Program of Mathematics Education of Unimed Postgraduate Program, 2014)
This study aims to determine how the context of public transportation in Indonesia (i.e. angkot), can be used to build students' reasoning and understanding the basic concepts of addition and subtraction of numbers to elementary students. As a result, design research was selected as an appropriate method to achieve the objectives of this study. In the approach to the research design, the sequence of learning activities are designed and developed based on the investigation of student learning process. 28 students and a teacher in grade 2 elementary schools in Indonesia (i.e. MIN-2 Palembang) involved in this study. The experimental results show that get on and get off of passengers in drama of public transportation, playing angkot-angkotan, can stimulate students to get ideas on number operations. Furthermore, the strategies and tools used by the students in the playing angkot-angkotan can be developed gradually, through modeling appears, the operation of addition and subtraction of integers. In activity-based learning experience for addition and subtraction operations numbers, modeling appears plays an important role in students' reasoning shifts from concrete experience in situational levels to the formal of mathematical concepts